THE INFLUENCE OF PROFIT SHARING RATIO ON THE FINANCIAL PERFORMANCE OF SHARIA PEOPLE'S FINANCING BANKS IN NORTH SUMATRA - Nasution, Nina Andriany (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
The purpose of this study was to evaluate the Financial Performance of Islamic People's Financing Banks (BPR) in North Sumatra. Specifically to analyze the effect of the Profit Sharing Ratio (PSR) on the Debt to Equity Ratio (DER). The research approach uses Quantitative with Panel Data Types from 2017 – 2021, Panel Data Multiple Linear Regression analysis techniques. The results of this study are: Profit Sharing Ratio has a positive and significant partial effect on the Debt to Equity Ratio (DER) at BPRS in North Sumatra. Keywords: Profit Sharing Ratio (PSR), Debt to Equity Ratio (DER) and Financial Performance